2014
DOI: 10.3233/nre-141144
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of an intensive task-oriented circuit training in Multiple Sclerosis patients with mild disability

Abstract: BACKGROUND: Exercise is well tolerated and induces relevant improvements in physical and mental functioning of persons with Multiple Sclerosis (MS). Unfortunately, due to the wide variety of symptoms and the broad range of exercise interventions, it is not possible to make unified exercise recommendation as to what type of exercise is safe and effective for persons with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…The results of this study follow a positive trend similar to the already published data of Chisari et al ( 33 ), in which a group of 17 patients with MS showed significant improvement in the TUG test and a positive trend in the SF-36 questionnaire. In another study published by Tramonti et al ( 14 , 15 ), a group of 15 patients with MS showed only an insignificant trend in TUG test, but a clear improvement in the MFIS and MSWS-12 questionnaires.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study follow a positive trend similar to the already published data of Chisari et al ( 33 ), in which a group of 17 patients with MS showed significant improvement in the TUG test and a positive trend in the SF-36 questionnaire. In another study published by Tramonti et al ( 14 , 15 ), a group of 15 patients with MS showed only an insignificant trend in TUG test, but a clear improvement in the MFIS and MSWS-12 questionnaires.…”
Section: Discussionsupporting
confidence: 91%
“…However, there are many difficulties in reacquiring independent gait after stroke due to the neurological disorder of the body and the psychological fear of falling (Fletcher and Hirdes, 2004; Fritz et al, 2007). Representative gait trainings for stroke patients in clinical practice include treadmill walking training (Lindquist et al, 2007), task-oriented circuit training (Chisari et al, 2014), imagery training (Braun et al, 2006), gait training in various obstacle courses (Dean et al, 2000), and virtual reality programs (Lord et al, 2004). However, these exercises are only available to the stable indoor environment and do not take into account the various environmental factors, which are required for patients to participate in community activities (Lord and Rochester, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The CCT programme in this study differed to the clinical trials in the literature with respect to dose and setting. Although many studies based in the inpatient setting provided CCT as much as five times per week (Blennerhassett & Dite, 2004;Chisari, Venturi, Bertolucci, Fanciullacci, & Rossi, 2014;English et al, 2007), 85% of our participants reported the frequency of classes as either excellent or good. Free-text comments related to this question highlighted that participants had other appointments they needed to attend and transportation was a challenge for some.…”
Section: Discussionmentioning
confidence: 61%